Isolated knee pain as a presentation for proximal femur fracture in paediatrics - Amirudin Sanip,; Ismail MS, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Proximal femur fracture in paediatric patients are very rare and can easily be missed especially when the history of trauma is so trivial, and associated with pathological fracture. We report a case of 6-year-old girl with a history of left knee pain following a fall from a height of 2 feet. She was treated as a soft tissue injury of the left knee as the left knee radiograph was normal. She was reassessed at day 3 of injury with worsening symptoms. Radiograph of the pelvis and left knee revealed a comminuted intertrochanteric fracture of left femur with an underlying bone cyst. We would like to highlight this case report to avoid missing a proximalfemur fracture where a trivial trauma resulted In the presentation of a non-specific knee pain. Femur fracture in peadiatric age group can result in the significant complication of growth such as osteoporosis.